2019
DOI: 10.5194/acp-19-11443-2019
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous in situ measurements of small-scale structures in neutral, plasma, and atomic oxygen densities during the WADIS sounding rocket project

Abstract: Abstract. In this paper we present an overview of measurements conducted during the WADIS-2 rocket campaign. We investigate the effect of small-scale processes like gravity waves and turbulence on the distribution of atomic oxygen and other species in the mesosphere–lower thermosphere (MLT) region. Our analysis suggests that density fluctuations of atomic oxygen are coupled to fluctuations of other constituents, i.e., plasma and neutrals. Our measurements show that all measured quantities, including winds, den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…(2012, 2013) and Strelnikov et al. (2019) at ∼69°N above Andøya, Norway. The (thin) blue dashed line was calculated for H' = 77 km and β = 0.7 km −1 for comparison with the slope of the H' = 77 km and β = 0.6 km −1 mean winter solid blue line and the slopes of the rocket observations.…”
Section: Comparisons With Others and Electron Number Densitiesmentioning
confidence: 88%
See 2 more Smart Citations
“…(2012, 2013) and Strelnikov et al. (2019) at ∼69°N above Andøya, Norway. The (thin) blue dashed line was calculated for H' = 77 km and β = 0.7 km −1 for comparison with the slope of the H' = 77 km and β = 0.6 km −1 mean winter solid blue line and the slopes of the rocket observations.…”
Section: Comparisons With Others and Electron Number Densitiesmentioning
confidence: 88%
“…(2013) (F13), and Strelnikov et al. (2019) (S19). The straight red dashed line is a ( H ′, β ) best fit to the rocket profile of December 4, 2010.…”
Section: Comparisons With Others and Electron Number Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for that was the relative simplicity of implementation and numerical stability of the Heisenberg (1948) model. Staszak et al (2021) and Strelnikov et al (2017Strelnikov et al ( , 2019) applied Lübken's technique utilizing both Heisenberg (1948) and Tatarskii (1971) models and showed that the results can reveal considerable discrepancies as far as absolute ɛ-values are concerned, however yielding very similar relative vertical structure and variability.…”
Section: Spectral Model Techniquementioning
confidence: 99%
“…While not fully resolvable by models, these subgrid‐scale processes can be observed by various observational techniques, including radar, lidar and rocket measurements (Le Pichon et al., 2015; Rapp & Lübken, 2004; Schäfer et al., 2020; Strelnikov et al., 2019). One such subgrid‐scale phenomenon is atmospheric gravity waves (GWs).…”
Section: Introductionmentioning
confidence: 99%